Website-Based Student Digital Report Card Design - Khairul; Alviona Marsya; Triyadi, M Dico; Irsyad, Muhammad (Bahasa Indonesia, 2023)
The use of computer technology continues to grow so that it has an impact on changes to a system, which was previously done manually, now the system can be computerized. Various education sectors, both formal and informal, continue to improve in various ways ranging from learning methods, learning media to learning outcomes that we know by the term report card. Digital report cards are not something that is classified as new in homeland education. Transferring grades that have been printed from the RDM (Raport Digital Madrasah) application to the report card book will take a long time because of the large number of students. A large number of grade data files will cause storage to accumulate. If there is a mistake in writing the value, searching for value data will take a long time. Not to mention some problems that occur when the report card given in the form of sheets of paper is wet, torn or lost which causes the school to have to reprint many times To overcome these problems, it is necessary to design a website-based digital report card information system that can be accessed by teachers, educators, and especially students. Schools need this system to managerialize student grade data, so that students and parents can view report card data online and anywhere as long as it is connected to an internet connection without the need to print it. System Development Life Cycle (SDLC) is the process of creating and changing systems and models and methodologies used to develop a system. The results obtained are a digital report card system that is practical to use and can minimize the risk of damage and loss of data hoping to help in retrieving student report cards more easily, can view data online, without the need to come to school.